Dynamic protein folding at the surface of stimuli‐responsive peptide fibrils. (14th March 2018) - Nagarkar, Radhika P.; Miller, Stephen E.; Zhong, Sheng; Pochan, Darrin J.; Schneider, Joel P.
Abstract: The repetitive self‐assembled structure of amyloid can serve as inspiration to design functional materials. Herein, we describe the design of α/β6, a peptide that contains distinct α‐helical and β‐structure forming domains. The folding and association state of each domain can be controlled by temperature. At low temperatures, the α‐domain favors a coiled‐coil state while the β‐domain is unstructured. Irreversible fibril formation via self‐assembly of the β‐domain is triggered at high temperatures where the α‐domain is unfolded. Resultant fibrils serve as templates upon which reversible coiled coil formation of the α‐domain can be thermally controlled. At concentrations of α/β6 ≥ 2.5 wt%, the peptide forms a mechanically defined hydrogel highlighting the possibility of designing materials whose function can be actively modulated by controlling the folded state of proteins displayed from the surface of fibrils that constitute the gel.